Bata, saan ka patungon [videoreocridng] - Jacob, Marilou (Communication Foundation for Asia, 1979)
A documentary on the condition of the under-privileged children, how they feel and react to such condition. The video uses music from the popular play, "Juan Tamban". Winner of a special award for the International Year of the Child at the 1979 Catholic Mass Media Awards.